Você é muito nova pra brincar de morrer... Uma etnografia com jovens e adolescentes que praticam a automutilação - Silva, Everton de Lima (2017)
This dissertation discusses the phenomenon known as self-mutilation. It is a practice usually linked to young people, mostly teenagers, and female, who have as one of their characteristics the fact that people hide their signs. Silenced in faceto- face everyday, self-mutilation, however, is visible and present in social networks, especially in WhatsApp. The research presented here followed this phenomenon, from the insertion of its researcher in several groups of WhatsApp and, to a lesser extent, of Facebook. Self-mutilation has an anti-structure, anomie aspect. The conduct of being cut is even represented in music as an "emergency exit". A selfmutilator can spend weeks without cutting himself and for some reason injure himself in a higher sequence than he or she may be coerced to stop cutting himself, can do therapy, substitute self-mutilation for some other conduct, among other attitudes. Trying to make a static picture about self-mutilation does not seem advisable, since one who cuts himself is often flirting with instability, flight, despair, appeal to pleasure, etc. What can you expect from a WhatsApp group for people who practice self-mutilation? There are a group of people who are fleeing from a host of other socialities that do not behave. I have said that the people with whom I live are fleeing from various socialities, even though they refer to and see "society" as a villain. In WhatsApp groups for people who cut themselves I see a place of refuge, where what guarantees acceptance is the condition of equality against selfmutilation. In these spaces people present themselves and represent themselves differently than when they are outside the group. In these groups, self-infiltrators are inventing their sociality through their agency, an agency that they call diffuse or negative by the very fact that, in their representations, self-perpetrators often associate their practice with suicide, suffering, and other afflictions.